SELF EFFICACY BERHUBUNGAN DENGAN KESADARAN PEMUDA SEBAGAI BYSTANDER CPR PADA HENTI JANTUNG DI LUAR RUMAH SAKIT DI MASA PANDEMI COVID-19 - Anissa Cindy Nurul Afni; Mila Wahyu Utami; Meri Oktariani; S.Dwi Sulisetyawati; Sutiyo Dani Saputro (Universitas Kusuma Husada Surakarta, 2023)
Peningkatan kasus henti jantung di luar rumah sakit (Out of Hospital Cardiac Arrest-OHCA) terjadi sejak pandemi Covid-19. Ditemukan variasi prognosis pada kasus OHCA akibat menurunnya tingkat keberhasilan dan bantuan resusitasi. American Heart Association (AHA) merekomendasikan untuk meningkatkan peran komunitas sebagai bystander salah satunya melalui pemuda. Pemuda mempunyai fisik yang kuat, sigap dan kemauan belajar yang tinggi, tetapi potensi pemuda sebagai bystander masih kurang berhubungan dengan kesadaran diri dan self efficacy. Self efficay erat dengan keengganan untuk membantu orang asing. Penelitian ini bertujuan menganalisis hubungan kesadaran dengan self efficacy pemuda sebagai bystander CPR pada henti jantung di masa pandemi Covid-19. Jenis penelitian ini adalah kuantitatif observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah pemuda Desa Waru Karangnayar sebanyak 210 anggota. Sampel diambil menggunakan teknik non probability sampling dengan jumlah 44 responden. Hasil uji chi-square menunjukkan p-value variabel kesadaran dengan self efficacy sebesar 0,006 (p<0,05) berarti bahwa ada hubungan antara kesadaran dengan self efficacy. Self efficacy adalah keyakinan individu mengenai kemampuan dirinya dalam melakukan tugas atau tindakan yang diperlukan untuk mencapai hasil tertentu. Seseorang yang mengenali dirinya tentu menyadari akan kemampuan diri pemuda yang sadar akan perannya, akan memiliki self efficacy yang tinggi untuk menghubungi Emergency Medical Service (EMS). Ketika seseorang sadar akan kejadian henti jantung maka efikasi diri pada seseorang tersebut akan timbul. Since the Covid-19 pandemic there had been an increase in cases of Out of Hospital Cardiac Arrest (OHCA). Variations of survival rate in OHCA cases due to decreased success rates and resuscitation assistance by bystender. The American Heart Association (AHA) recommends increasing the role of the community as bystanders, one of which is addolscents. Young people are physically strong, alert and have a high willingness to learn, but their potential as bystanders is still lacking due to a lack of self afficy. Self efficacy relates to reluctance to help strangers. This purpose of this study was to analyze the relationship between self-efficacy anda awareness addolscents as bystanders CPR in cardiac arrest during the Covid-19 pandemic. The type of research is quantitative observational analytic with a cross sectional approach. The population in this study were the addolscents of Waru Karangnayar Village with 210 members. Sampling used non-probability sampling technique with 44 respondents. Data analysis used the chi-square test. The results showed that the p-value of the variable awareness with self-efficacy is 0.006 (p <0.05) meaning that there is a relationship between self-efficacy and awareness. Self efficacy is an individual's belief about his ability to perform tasks or actions needed to achieve certain results. Someone who knows himself is certainly aware of his own abilities. The Covid-19 pandemic continues to increase and spread widely, giving rise to challenges faced, namely ensuring victims of cardiac arrest without or confirmed Covid-19 get first aid and a chance to live without endangering the safety of helpers. Situation self-awareness is the awareness a person has of a particular situation and an understanding of what is going on. As a bystander, young people who are aware of their role will have high self-efficacy in contacting the Emergency Medical Service (EMS). When a person is aware of the occurrence of cardiac arrest, self-efficacy in that person will arise.